Urban Tourism of Yogyakarta - Soekadri, Soekadri (Universitas Muhammadiyah Surakarta, 1999)
Yogyakarta city principally be able to develop as an urban tourism. The international altraction i.e. Malioboro has been growth over the world, and being the first nesessary objet for paying attention beside the other tourism object as an old Cina building, old Europe building, and Javanese traditional houses also classical Javanese musi (gamelan) and dancing, and not to be forgotten is the special various Javanese food (gastronomi). The serious problems up till now exist is city transportation specially tourism transportation not supporting efficienly and also nicely mode for getting all potential city tourism location. Uplevelling rural tourism (rural â urban) potential more or less was still forgetted, so the socio economic, value losses by feelingness way. In the near future programme and planning for supporting the Yogyakarta City to the urban tourism is very strategic and very importance especially develop the tourism attraction object as well as seriously by linking all urban activities tourism to rural area tourism at the surrounding Yogyakarta special teritorry. Rural urban linkages model will be the nicely tool, with more special attention to all attraction potential tourism object are develop who supported the local rural people and special policy programme.